Determinants of Family Resilience in Female-Headed Families on the North Coast of Java - Mohammad Noviani Ardi; Tali Tulab; Dina Yustisi Yurista; Aliyatus Sariroh (IAIN Manado, 2022)
This study analyzes the relationship between religiosity, education, and social support to family resilience in women-headed households. Family resilience is an exciting issue discussed today, seeing the fragility of the couple's understanding based on the family itself. It is essential because it protects from life problems and difficulties arising from the internal or external family, including groups, environments, communities, and countries. The results of this study contribute to efforts to increase family resilience, especially in women-headed homes, because family resilience is the main foundation in realizing community resilience as one of the efforts to boost national development. The power of national development is sourced to families as small groups in society. Thus, an in-depth study of the factors that affect family resilience to create a prosperous family, resistance, and continuity of national development is needed. The research method uses a quantitative approach and collects data using surveys of 15-20 women-headed households in Sayung, Demak. Data analysis is carried out with Validity Test, Reliability Test, and Regression Analysis using SPSS software. This study showed that education positively and significantly affects family resilience. In contrast, religiosity and social support have a positive and insignificant impact. The government can be used as a reference in decision-making to help economic resilience in women-headed households by making programs to increase family resilience in economics.